Association of IL-6 rs1800796 Gene Polymorphism on Susceptibility to Pulmonary Tuberculosis - Maria Kristiani; Yani Jane Sugiri; Iin Nor Chozin; Nanik Setiyowati; Aditya Sri Listyoko (Jurnal Respirasi, 2022)
Introduction: IL-6 is a pro-inflammatory cytokine controlling the immune response to TB. This study investigated the association of IL-6 rs1800796 gene polymorphism on susceptibility to pulmonary TB. Methods: The case-control study involved 71 cases and 34 controls. Blood samples were taken from all study participants at Dr. Saiful Anwar General Hospital, Malang, between August 2020 and February 2021. Blood samples were used in a genotyping investigation to determine SNPs using the PCR-Multiplex technique. Results: The genotype association of IL-6 rs1800796 (G/G, G/C, C/C) and allele frequency for patients and controls of IL-6 rs1800796 with susceptibility to pulmonary TB were insignificant (p > 0.05). Conclusion: This study found no evidence of an association of IL-6 rs1800796 gene polymorphism with susceptibility to pulmonary TB.